Pengembangan Usaha Produksi Gula Tebu Buk Nini Dan Manfaatnya Untuk Kesehatan Di Nagari Lawang Sumatera Barat - Rosa, Yenni Del; Abdilla, Mohammad; Yendra, Nofri; Riski, Tri Rachmat; Rahmasari, Nisya Cesaryani (LPPM Universitas Dharma Andalas, 2025)
Mrs. Nini's sugarcane sugar production business has lacked appropriate information technology. Her maximum turnover is only around Rp 1,000,000 per week, with a selling price of Rp 3,000 per glass of sugarcane juice and Rp 25,000 per pack of sugarcane sugar. The sugarcane production process employs 3-4 family members. Marketing of the sugarcane sugar is limited to local needs. The prospects for this sugarcane sugar business are quite good due to the continuous daily demand for sugarcane as a raw material for making soy sauce. Priority issues for Mrs. Nini's sugarcane production business include marketing strategies and the health impacts of sugarcane (sugarcane juice) consumption. The training method involves lectures, discussions, and practical exercises. The goal is to educate partners about various marketing strategies and the health impacts of sugarcane (sugarcane juice) consumption. Mrs. Nini's sugarcane production requires a sugarcane milling press and a sugarcane juice mixer. The marketing strategy involves maintaining existing markets and quality, exploring new markets, and exploring alternative marketing channels using digital marketing. The impact of consuming cane sugar (sugarcane juice) on health is quite numerous, such as increasing the body's metabolism, meeting energy needs, maintaining digestive health and helping reduce constipation.